Effectiveness of an impedance cardiography guided treatment strategy to improve blood pressure control in a real-world setting: results from a pragmatic clinical trial - Yuan Lu; Jianlei Gu; Harlan Krumholz; Hongyi Wang; Zhiying Zhang; Ningling Sun; Luyan Wang; Zheng J Ma; Zheng Lian (Open Heart)
Objective To test the effectiveness of an impedance cardiography (ICG) guided treatment strategy on improving blood pressure (BP) control in real-world clinical practice.Design A single-centre, pragmatic randomised trial.Setting A hypertension clinic of the Peking University People’s Hospital in Beijing, China.Participants Adults who sought outpatient care for hypertension in the hypertension clinic at the Peking University People’s Hospital between June and December 2019.Interventions A computerised clinical decision support of recommending treatment choices to providers based on patients’ haemodynamic profiles measured by ICG.Main outcome measures Changes in systolic BP (SBP) and diastolic BP (DBP) levels at the follow-up visit 4–12 weeks after baseline. Secondary outcomes included achievement of BP goal of <140/90 mm Hg and the changes in BP by baseline BP, age, sex and body mass index (BMI).Results A total of 102 adults (mean age was 54±14 years; 41% were women) completed the study. The mean baseline SBP was 150.9 (SD of 11.5) mm Hg and mean baseline DBP was 91.1 (11.3) mm Hg. At the follow-up visit, the mean SBP and DBP decreased by 19.9 and 11.3 mm Hg in the haemodynamic group, as compared with 12.0 and 4.9 mm Hg in the standard care group (p value for difference between groups <0.001). The proportion of patients achieving BP goal of <140/90 mm Hg in the haemodynamic group was 67%, as compared with 41% in the standard care group (p=0.017). The haemodynamic group had a larger effect on BP reduction consistently across subgroups by age, sex, BMI and baseline BP.Conclusions An ICG-guided treatment strategy led to greater reductions in BP levels than were observed with standard care in a real-world population of outpatients with hypertension. There is a need for further validation of this strategy for improving blood pressure treatment selection.Trial registration number NCT04715698.